Emergence of Cooperation in Anonymous Social Networks Through Social Capital - Immorlica, Nicole; Lucier, Brendan; Rogers, Brian (ACM Conference on Electronic Commerce 2010 and Workshop on Information in Networks (WIN) 2010, 2010)
We study the emergence of cooperation in dynamic, anonymous social networks, such as in online communities. We examine prisoner’s dilemma played under a social matching protocol, where individuals form random links to partners with whom they can interact. Cooperation results in mutual benefits, whereas defection results in a high short-term gain. Moreover, an agent that defects can escape reciprocity by virtue of anonymity: it is always possible for an agent to abandon his history and re-enter the network as a new user. We find that cooperation is sustainable at equilibrium in such a model. Indeed, cooperation allows an individual to interact with an increasing number of other cooperators, resulting in the formation of a type of social capital. This process arises endogenously, without the need for potentially harmful social enforcement rules. Additionally, for a rich class of parameter settings, our model predicts a stable coexistence of cooperating and defecting agents at equilibrium.